The Nexus between CO2 Emissions and Health Expenditure – Causality Evidence from Selected CEE Countries - Bölükbaş, Mehmet; Szymańska, Agata (Comparative Economic Research. Central and Eastern Europe, 2025)
Greenhouse gas emissions, primarily carbon dioxide (CO2), influence climate change and have a significant impact on public health. The relationship is a subject of interest to many researchers. However, the situation of Central and Eastern European (CEE) countries is not sufficiently explored in this context. Thus, this study examines the linkages between CO2 emissions and health expenditures in 11 CEE countries. The empirical findings obtained using Kónya’s bootstrap panel Granger causality test show that CO2 emissions and health expenditures are related in most CEE countries. Notably, a bidirectional relationship in the bootstrap panel Granger causality test is found for Croatia, Romania, and Slovakia. In contrast, the relationship was revealed to be insignificant in Bulgaria, Lithuania, Poland, and Slovenia. The results are significant and contribute to the existing literature. The findings allow us to issue policy recommendations to intensify efforts to control pollution, particularly CO2 emissions, especially in Croatia, Romania, and Slovakia, as well as in the countries where at least unidirectional effects from CO2 emissions to health expenditures were observed (e.g., Estonia, Hungary, and Latvia).